The Influence of Leadership Style and Work Facilities on Job Satisfaction and Its Impact on Employee Performance at Bank Jambi Muara Sabak Branch Office - Diki Kurniawan; Pantun Bukit; Ali Akbar (Journal of Accounting and Finance Management, 2026)
This study aims to obtain an overview of leadership styles, work facilities, job satisfaction, and employee performance at Bank Jambi Muara Sabak Branch Office. It also aims to determine and analyze the influence of leadership styles and work facilities on employee performance, both directly and indirectly through job satisfaction. This research was conducted at the Muara Sabak Branch of Bank Jambi. The population consisted of 54 employees, using saturated sampling. This study employed a quantitative approach with a survey method and Partial Least Squares (PLS) data analysis. The research results show that leadership style and work facilities influence employee performance, both directly and indirectly through employee job satisfaction. This indicates that leadership that creates a supportive work environment, supported by the availability and quality of adequate work facilities, will increase job satisfaction, which ultimately contributes to improved employee performance.